CHARACTER BUILDING IN NEW NORMAL ISLAMIC EDUCATION - Dianto Dianto (Proceeding International Seminar of Islamic Studies, 2021)
The Covid 19 pandemic period is a challenge in all fields, one of which is education. In this new normal era, let us as people who are responsible in the world of education, must have high enthusiasm and maximum hard work, so that education in Indonesia can be more advanced. This article aims to describe how to shape children's character in the new normal era by providing various information involving educators, parents and people involved in the distance learning process. During the Covid 19 pandemic, we see that online system learning has greatly increased in digital use. With the development of online learning that is done well, it can form a generation with good character according to the ideals of National education. So the existence of educators is also important to achieve these lofty goals. Although the pandemic limits face-to-face space, educators must be present to continue its mission. Between educators, parents, and students there must be synergy as part of efforts to build national character. The last hope is that Islamic education in the midst of the digital flow will be the best defense and lead them to grow into a digital generation with character. Keywords: Shaping Character, Islamic Education, New Norma